Patterns of Recurrent Thrombosis in Primary Antiphospholipid Syndrome—Multicenter, Real-Life Long-Term Follow-Up - Stanley Niznik; Micha J. Rapoport; Micha J. Rapoport; Orly Avnery; Aharon Lubetsky; Aharon Lubetsky; Soad Haj Yahia; Soad Haj Yahia; Martin H. Ellis; Martin H. Ellis; Nancy Agmon-Levin; Nancy Agmon-Levin (Frontiers in Immunology, 2022)
BackgroundAntiphospholipid syndrome (APS) is an acquired hypercoagulable condition associated with antiphospholipid antibody (aPL) presence. Data on re-thrombosis following APS-diagnosis are limited.MethodsThis is a retrospective analysis of new thrombotic events among primary APS (pAPS) patients followed for up to 15 years in three medical centers in Israel.ResultsAmong 312 primary-APS patients, 143 (46%) had new thrombotic event classified to three patterns: (1) Arterial—associated with heart valve disease (OR 7.24, 95% C.I. 2.26–24.6), hypertension (OR 3, 95% C.I. 1.44–6.25), elevated anti-B2-GPI IgM (OR 1.04, 95% C.I. 0.996–1.08), arterial thrombosis at presentation (OR 1.74 95% C.I. 0.992–3.26), and older age (41 vs. 34 years, p < 0.001). (2) Venous—linked with venous thrombosis at presentation (OR 12.9, 95% C.I. 5.27–31.6, p < 0.001), heart valve disease (OR 9.81 95% C.I. 1.82–52.9, p = 0.018), aGAPSS (OR 1.15 95% C.I. 1.02–1.29), and younger age (31 vs. 36.5 years, p = 0.001); and (3) Combined pattern—associated with heart valve disease (OR 40.5 95% C.I. 7.7–212) and pulmonary embolism (OR 7.47 95% C.I. 1.96–28.5). A 4th variant “the Breakthrough pattern” defined by re-thrombosis despite prophylactic therapy was observed in 100/143 (70%) patients and linked with heart valve disease (OR 8. 95% C.I. 2.43–26.3), venous thrombosis at presentation (OR 2.61 95% C.I. 1.47–4.66), leg ulcers (OR 12.2, 95% C.I. 1.4–107), hypertension (OR 1.99, 95% C.I. 0.92–4.34), and higher aGAPSS (OR 1.08, 95% C.I. 0.99–1.18).ConclusionIn this real-life observation, re-thrombosis was common among pAPS patients including in those recommended to receive prophylactic therapy. Different patterns of recurrence were identified and linked with presenting symptoms, specific serological markers, APS manifestations, and comorbidities. Studies that will address interventions to prevent recurrences of APS-related events are needed.